1986
DOI: 10.1172/jci112339
|View full text |Cite
|
Sign up to set email alerts
|

Inverse relationship of leucine flux and oxidation to free fatty acid availability in vivo.

Abstract: To determine the effect of fatty acid availability on leucine metabolism, 14-h fasted dogs were infused with either glycerol or triglyceride plus heparin, and 46-h fasted dogs were infused with either nicotinic acid or nicotinic acid plus triglyceride and heparin. Leucine metabolism was assessed using a simultaneous infusion of L-14,5-3H]leucine and a-[1-'4Cjketoisocaproate. Leucine, a-ketoisocaproate (KIC), and totalleucine carbon (leucine plus KIC) flux and oxidation rates were calculated at steady state. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 31 publications
6
39
0
1
Order By: Relevance
“…However, we cannot exclude the possibility that a resistant state to insulin and/or amino acids produced by TNF-␣ was at least partially responsible for the diminished rate of synthesis (29). Elevations in plasma FFAs have been shown to be capable of modulating protein balance in vivo (47). However, no significant alterations in plasma FFA concentrations were detected in TNF-␣-infused rats.…”
Section: Discussionmentioning
confidence: 84%
“…However, we cannot exclude the possibility that a resistant state to insulin and/or amino acids produced by TNF-␣ was at least partially responsible for the diminished rate of synthesis (29). Elevations in plasma FFAs have been shown to be capable of modulating protein balance in vivo (47). However, no significant alterations in plasma FFA concentrations were detected in TNF-␣-infused rats.…”
Section: Discussionmentioning
confidence: 84%
“…However, we cannot exclude that factors other than insulin deficiency per se might have been responsible for the results observed. Insulin withdrawal was associated with a significant increase in the plasma concentration ofcortisol, glucagon, FFA, ketone bodies, and essential amino acids which have been reported to affect leucine and protein metabolism (13,15,56,58,(70)(71)(72)(73)(74)(75). However, in absence of other hormonal inter-actions in vitro, insulin deficiency decreased the rate of albumin gene transcription and, conversely, insulin replacement increased it (28).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic response of our obese ZDF rats is probably more similar to the fair adaptation of obese subjects to starvation: these subjects had better nitrogen preservation than lean subjects and have been shown to be able to survive longer during hunger strike [43,44]. The hypothetical 'protective effect' of obesity post-injury may be related to a possible sparing action of fat on protein metabolism [45][46][47]. In fasted obese patients, an inverse relationship has been shown between urinary nitrogen excretion and level of adiposity in both human and animal models, suggesting a protein-sparing effect of lipids [45].…”
Section: Effect Of Food Restrictionmentioning
confidence: 81%
“…These authors reported an increase in both protein turnover and leucine oxidation in the lean subjects during short-term starvation, whereas there were no significant changes in the obese subjects [45]. One elegant study [46] demonstrated an inverse relationship between leucine oxidation and NEFA levels (and NEFA oxidation) in dogs. In humans, a moderate increase in NEFA (nearly 1 mmol/l) also resulted in a 20% reduction in leucine oxidation [47].…”
Section: Effect Of Food Restrictionmentioning
confidence: 99%